JUNOS OS for dummies - Goralski, Walter (Wiley, 2011)
Learn to use JUNOS to make your network reliable! Providing network administrators with a reliable network operating system, JUNOS software is an award-winning network operating system that focuses on security and the avoidance of down time. This easy-to-understand book starts with the basics of JUNOS and walks you through its features so that you can quickly learn how to set up, operate, and add key services. Since the various JUNOS features are constantly being updated to provide your network with the best security possible, this new edition shares must-know information, helpful advice, hand.
Print version record
Keywords: Juniper Networks, Inc; Routers (Computer networks); Computer network protocols; Computer networks -- Equipment and supplies; Routeurs (Réseaux d'ordinateurs); Protocoles de réseaux d'ordinateurs; COMPUTERS; Networking; Network Protocols; Computer networks; Equipment and supplies